2011
DOI: 10.1016/j.apm.2010.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Selecting optimum maintenance strategy by fuzzy interactive linear assignment method

Abstract: a b s t r a c tIn the current competitive environment managers of manufacturing and service organizations try to make their organizations competitive by providing timely delivery of high quality products. Maintenance, as a system, plays a key role in reducing cost, minimizing equipment downtime, improving quality, increasing productivity and providing reliable equipment and as a result achieving organizational goals and objectives. This paper presents a new approach for selecting optimum maintenance strategy u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(58 citation statements)
references
References 30 publications
(51 reference statements)
1
51
0
Order By: Relevance
“…This process is repeated for observations until a predetermined acceptable value of the error is achieved, usually using the mean square error (MSE), which is defined in (13). To ensure a rapid convergence of the iterative method, we usually use mathematical optimization methods; in this case, we use Bayesian Regularization [38].…”
Section: Phase Of Analysis Through Machine Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…This process is repeated for observations until a predetermined acceptable value of the error is achieved, usually using the mean square error (MSE), which is defined in (13). To ensure a rapid convergence of the iterative method, we usually use mathematical optimization methods; in this case, we use Bayesian Regularization [38].…”
Section: Phase Of Analysis Through Machine Learningmentioning
confidence: 99%
“…Thus, the literature review, carried out by Mardani et al [12] about the fuzzy multiple criteria decision-making techniques, found that, in maintenance environments, the fuzzy approach is utilized in strategic framework, in the long term as, for example, in the selection of the maintenance strategy [13][14][15] or the maintenance policy [16]. This could be extensible to projects [17,18] or in civil engineering [19] environments where there is more uncertainty due to the different conditions of each event.…”
Section: Introductionmentioning
confidence: 99%
“…Their model has the capacity to reduce cost due to failure. Bashiri et al [5] used a fuzzy interactive linear assignments method to determine optional selection strategy for maintenance system. The method was claimed to be easily adaptable by managers.…”
Section: Maintenance and Sustainability Issuesmentioning
confidence: 99%
“…Garcia et al [14] present application of Intelligent System for Predictive Maintenance (SIMAP) to the health condition monitoring of a wind turbine gearbox. Katchasuwanmanee et al [15] propose a thermal and energy-management prototype system e-ProMan for application in SME manufacturing environments.…”
Section: Introductionmentioning
confidence: 99%
“…Although this method considers both strategic, technical and managerial criteria, it does not build any relationship between management and technical requirements. Bashiri et al [14] present an approach for selecting optimum maintenance strategy using both qualitative and quantitative data through interactions with the maintenance experts based on linear assignment method (LAM) with interactive fuzzy linear assignment method (IFLAM). Chemweno et al [19] propose a risk assessment technique in maintenance decision-making domain using the analytic network process.…”
Section: Introductionmentioning
confidence: 99%